Bilevel positive airway pressure ventilation for non-COPD acute hypercapnic respiratory failure patients: A systematic review and meta-analysis - Bandar M Faqihi (Wolters Kluwer Medknow Publications, 2021)
The effectiveness of bi-level positive airway pressure (BiPAP) in patients with acute hypercapnic respiratory failure (AHRF) due to etiologies other than chronic obstructive pulmonary disease (COPD) is unclear. To systematically review the evidence regarding the effectiveness of BiPAP in non-COPD patients with AHRF. The Cochrane Library, MEDLINE, EMBASE, and CINAHL Plus were searched according to prespecified criteria (PROSPERO-CRD42018089875). Randomized controlled trials (RCTs) assessing the effectiveness of BiPAP versus continuous positive airway pressure (CPAP), invasive mechanical ventilation, or O2 therapy in adults with non-COPD AHRF were included. The primary outcomes of interest were the rate of endotracheal intubation (ETI) and mortality. Risk-of-bias assessment was performed, and data were synthesized and meta-analyzed where appropriate. Two thousand four hundred and eighty-five records were identified after removing duplicates. Eighty-eight articles were identified for full-text assessment, of which 82 articles were excluded. Six studies, of generally low or uncertain risk-of-bias, were included involving 320 participants with acute cardiogenic pulmonary edema (ACPO) and solid tumors. No significant differences were seen between BiPAP ventilation and CPAP with regard to the rate of progression to ETI (risk ratio [RR] = 1.49, 95% confidence interval [CI], 0.63–3.62, P = 0.37) and in-hospital mortality rate (RR = 0.71, 95% CI, 0.25–1.99, P = 0.51) in patients with AHRF due to ACPO. The efficacy of BiPAP appears similar to CPAP in reducing the rates of ETI and mortality in patients with AHRF due to ACPO. Further research on other non-COPD conditions which commonly cause AHRF such as obesity hypoventilation syndrome is needed.